Lifestyle modification factors in hypertensive patients: impact on blood pressure variability - Dotsenko, N. Ya.; Boev, S. S.; Shekhunova, I. A.; Нerasуmenko L. V.; Molodan, A. V.; Malinovskaya , A. Ya. (Modern medical technology, 2021)
Current guidelines do not suggest considering blood pressure variability in the management of hypertensive patients. At the same time, a sufficient evidence base has been accumulated on the relationship of blood pressure variability with damage to target organs, the development of stroke, myocardial infarction, cardiovascular mortality, and kidney disease. In general, assessing the effect of blood pressure variability on the course of arterial hypertension, it can be assumed that it is not as significant as the absolute values of blood pressure, but this effect has been proven, regardless of the degree of hypertension. And if a practitioner finds an increased variability in blood pressure in his patient, he should know what recommendations should be given to him. Not all traditional lifestyle modification factors that are suggested for hypertensive patients affect blood pressure variability in the same way as blood pressure readings. Thus, we were unable to find evidence of the influence of increased consumption of table salt, physical activity, «chronic psychological stress» on the variability of blood pressure in the general population. At the same time, dietary habits, alcohol abuse, smoking status affect the level of blood pressure, blood pressure variability in both healthy individuals and patients with arterial hypertension. The same effect is exerted by the relative intake of minerals with food, toxic agents (lead). If in individuals of the general population an increase in body weight leads to an increase in blood pressure, then in patients with arterial hypertension such an effect is nonlinear, depending on the type of obesity. It should be emphasized once again that the presence of psychoemotional disorders symptoms of anxiety, depression – in patients with arterial hypertension contributes both to an increase in the level of blood pressure, but also to its variability.